Heat-conducting silicone adhesive and preparation method thereof

By introducing a composite thermal conductive material of modified hexagonal boron nitride, carbon fiber and CuO NPs nanomaterials, the problems of poor thermal conductivity and easy aging of silicone adhesive at high temperatures are solved. The excellent thermal conductivity, mechanical and high temperature resistance of thermal conductive silicone adhesive are achieved, and the service life of electronic devices is improved.

CN120665432APending Publication Date: 2025-09-19FOSHAN YUANTONG ADHESIVE IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510927526.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing silicone adhesives have poor thermal conductivity under high temperature conditions and are prone to aging, which reduces the service life of electronic devices.

Method used

Modified hexagonal boron nitride, carbon fiber and CuO NPs nanomaterials were used as composite thermal conductive materials, combined with hydroxyl-terminated polydimethylsiloxane, fumed silica, etc., and thermally conductive silicone adhesive was prepared through ball milling, ultrasonic dispersion and vacuum stirring.

Benefits of technology

The thermal conductivity, mechanical properties and high temperature resistance of silicone adhesive are improved, and its aging resistance and durability are enhanced, making it suitable for use as an insulating layer material for electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005485196210000101
    Figure BDA0005485196210000101
  • Figure BDA0005485196210000111
    Figure BDA0005485196210000111
  • Figure BDA0005485196210000121
    Figure BDA0005485196210000121
Patent Text Reader

Abstract

The invention discloses a heat-conducting silicone adhesive and a preparation method of the heat-conducting silicone adhesive. The heat-conducting silicone adhesive is prepared from the following raw material components in parts by weight: 100 to 120 parts of hydroxyl-terminated polydimethylsiloxane, 20 to 30 parts of fumed silica, 5 to 8 parts of vinyl silicone oil, 3 to 5 parts of hydrogen-containing silicone oil, 0.001 to 0.002 part of a platinum catalyst, 20 to 30 parts of a composite heat-conducting material, 3 to 5 parts of a cross-linking agent and 3 to 8 parts of gamma-glycidyl ether oxypropyl trimethoxy silane, 0.1 to 0.5 part of dibutyltin dilaurate; the composite heat conduction material is selected from modified hexagonal boron nitride, carbonized fiber and a CuO NPs nano material. Compared with the prior art, the heat-conducting silicone adhesive prepared by the invention not only has better heat-conducting property, but also has good mechanical property and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicone adhesives, and in particular to a thermally conductive silicone adhesive and a preparation method thereof. Background Art

[0002] In recent years, with the continuous development of sophisticated electronic devices such as mobile phones and computers, electronic device materials have gradually become an important foundational material for my country's national economy. Currently, the insulating layer materials used in electronic devices are mostly organic resins such as epoxy resins and polyurethanes. However, epoxy resins and polyurethanes have significant defects in actual applications, which is not conducive to the application and development of insulating layer materials for electronic devices. In recent years, silicone adhesive materials have developed into the most commonly used insulating layer materials for electronic devices. Silicone adhesive materials have a Si-O-Si main chain structure. The Si-O backbone gives silicone adhesives excellent insulation properties, high and low temperature resistance, radiation resistance, and aging resistance. They are widely used in medical equipment, the automotive industry, electronic equipment and other fields.

[0003] Since electrical equipment generates a large amount of heat during operation, the silicone adhesives currently on the market have problems such as difficulty in heat dissipation and easy aging under long-term high temperature conditions, which greatly reduces the service life of electronic devices. Therefore, it is necessary to provide thermally conductive silicone adhesives and their preparation methods.

[0004] CN116179148A discloses a silicone adhesive and its preparation method and application. The silicone adhesive described in the invention contains the following components in parts by weight: 100 parts of polydimethylsiloxane, 100-120 parts of modified nano-calcium carbonate, 2-6 parts of antibacterial powder, 6-10 parts of thermally conductive silicone gel, 4-8 parts of a cross-linking agent, 0.2-0.8 parts of a coupling agent, and 0.02-0.2 parts of a catalyst; the thermally conductive silicone gel contains divinyl silicone oil, hydrogen-containing silicone oil, and an inorganic thermally conductive filler. The silicone adhesive prepared by the invention has good anti-aging and high-temperature resistance, but the thermal conductivity of the silicone adhesive is not ideal, which may significantly reduce the service life of electronic devices in practical applications.

[0005] CN116836676A discloses a yellowing-resistant thermally conductive potting silicone and its preparation method. The invention provides a yellowing-resistant thermally conductive potting silicone comprising component A and component B. Component A, in parts by weight, comprises the following raw materials: 45-55 parts of hydroxy-terminated polydimethylsiloxane, 10-15 parts of polylaurolactam, 50-60 parts of thermally conductive powder, 0.5-1 part of white carbon black, 2-5 parts of hydrogenated silicone oil, 0.5-1 part of coupling agent, and 0.5-1 part of catalyst. Component B, in parts by weight, comprises 20-30 parts of a curing agent. The yellowing-resistant thermally conductive potting silicone prepared by this invention has the advantages of high shear bonding strength, good yellowing resistance, and good thermal conductivity. However, the yellowing-resistant thermally conductive potting silicone has poor high-temperature resistance and cannot be used for long periods of time at high temperatures, resulting in poor anti-aging properties of the silicone adhesive. Summary of the Invention

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a thermally conductive silicone adhesive prepared by introducing modified hexagonal boron nitride, carbonized fiber, and CuO NPs nanomaterials as a composite thermally conductive material, mixing them with a base material and other additives. The thermally conductive silicone adhesive provided by the present invention not only has good thermal conductivity, but also excellent mechanical properties and high-temperature resistance. In addition, the introduction of CuO NPs nanomaterials also imparts excellent antibacterial properties to the silicone adhesive, greatly improving its durability.

[0007] To achieve the above objectives, the present invention provides a thermally conductive silicone adhesive comprising the following components in parts by weight: 100-120 parts of hydroxyl-terminated polydimethylsiloxane, 20-30 parts of fumed silica, 5-8 parts of vinyl silicone oil, 3-5 parts of hydrogenated silicone oil, 0.001-0.002 parts of a platinum catalyst, 20-30 parts of a composite thermally conductive material, 3-5 parts of a crosslinking agent, 3-8 parts of γ-glycidyloxypropyltrimethoxysilane, and 0.1-0.5 parts of dibutyltin dilaurate.

[0008] Preferably, the composite thermal conductive material is selected from at least two of modified hexagonal boron nitride, carbonized fiber, and CuO NPs nanomaterials.

[0009] Further preferably, the composite thermal conductive material is formed by mixing modified hexagonal boron nitride and carbonized fiber in a weight ratio of 5:1-3.

[0010] Further preferably, the composite thermal conductive material is formed by mixing modified hexagonal boron nitride and CuO NPs nanomaterials in a weight ratio of 5:0.5-1.

[0011] Further preferably, the composite thermal conductive material is formed by mixing modified hexagonal boron nitride, carbonized fiber and CuO NPs nanomaterial in a weight ratio of 5:1-3:0.5-1.

[0012] Preferably, the preparation method of the modified hexagonal boron nitride comprises the following steps:

[0013] Hexagonal boron nitride and polysaccharide are mixed uniformly in a weight ratio of 1:4-6 and placed in a ball mill jar. 3-5 mm zirconium oxide ball milling beads are added to 1 / 3-1 / 4 of the volume of the ball mill jar, and then ball milled at a speed of 15-20 Hz for 8-12 hours. The ball milled product is then washed with water 2-3 times, and then centrifuged at 4000-6000 rpm for 8-12 minutes. The precipitate is collected and vacuum dried at 40-50° C. to obtain modified hexagonal boron nitride.

[0014] Alternatively, hexagonal boron nitride and polysaccharide are mixed evenly in a weight ratio of 1:4-6 and placed in a ball mill, 3-5 mm zirconium oxide ball milling beads are added to 1 / 3-1 / 4 of the volume of the ball mill, and then ball milled at a speed of 15-20 Hz for 8-12 hours; the ball milled product is then washed with water 2-3 times, and then placed at 4000-6000 rpm for 8-12 minutes. The precipitate is collected and vacuum dried at 40-50 ° C to obtain a mixture; the mixture is immersed in a dopamine solution and mixed and stirred for 3-6 hours, wherein the immersion material-liquid ratio is 1:10-13, and then vacuum dried to obtain modified hexagonal boron nitride.

[0015] Preferably, the polysaccharide is selected from sucrose and chitosan oligosaccharide.

[0016] Preferably, the dopamine solution is obtained by mixing dopamine hydrochloride and Tris buffer in a weight ratio of 0.05-0.15:25.

[0017] Preferably, the method for preparing the carbonized fiber comprises the following steps:

[0018] The plant fiber is placed in a tubular furnace and carbonized under an argon atmosphere to obtain the obtained product. The carbonization process comprises the following steps: heating from room temperature to 115-125°C at a heating rate of 8-12°C / min and maintaining the temperature for 0.5-1.5h; then heating from 115-125°C to 350-370°C at a heating rate of 3-6°C / min and maintaining the temperature for 2-4h; and finally heating to 950-1050°C at a heating rate of 1-4°C / min and maintaining the temperature for 1.5-2.5h.

[0019] Preferably, the preparation method of the CuO NPs nanomaterial comprises the following steps, in parts by weight:

[0020] 2-4 parts of CuSO4·5H2O are mixed with 90-110 parts by weight of water, followed by adding 45-50 parts by weight of a plant extract, and maintaining the pH at 6.8-7.2 with a 0.1-0.2 mol / L NaOH aqueous solution. The solution is then mixed and reacted at 65-75°C and 400-600 rpm for 3-6 hours to obtain a mixed solution. The mixed solution is centrifuged at 800-1200 rpm for 20-25 hours, and the solid precipitate is washed 2-3 times with water and anhydrous ethanol in sequence, and then vacuum dried at 55-65°C for 3-5 hours to obtain CuO NPs nanomaterials.

[0021] Preferably, the plant extract is selected from one of neem leaf extract and Morinda officinalis leaf extract.

[0022] Preferably, the plant fiber is selected from flax fiber, ramie fiber and bamboo fiber.

[0023] Preferably, the crosslinking agent is a mixture of methyltrimethoxysilane and vinyltriethoxysilane in a weight ratio of 2-3:1.

[0024] Preferably, the platinum catalyst is a Karstedt' catalyst.

[0025] The present invention also provides a method for preparing the above-mentioned thermally conductive silicone adhesive, comprising the following steps:

[0026] (1) placing the composite thermal conductive material in a ball mill and dispersing it under the assistance of 20-50kHz ultrasound for 20-30min to obtain a pretreated composite thermal conductive material; then mixing the pretreated composite thermal conductive material and γ-glycidyloxypropyltrimethoxysilane at 1000-1500rpm and 45-60°C for 8-12min to obtain a mixture 1; adding the mixture 1 to a reactor, adding hydroxyl-terminated polydimethylsiloxane and fumed silica in sequence, mixing and stirring at 200-500rpm for 3-8min, then increasing the speed to 1000-1500rpm and mixing and stirring for 15-30min; then maintaining the speed of 1000-1500rpm, continuing to stir under vacuum at 75-85°C for 15-30min to obtain a mixture 2;

[0027] (2) Vinyl silicone oil and hydrogenated silicone oil are mixed with mixture 2, and the mixture is stirred under vacuum at 75-85°C and 1000-1200 rpm for 15-30 min; then a platinum catalyst is added, and the mixture is stirred at 75-85°C and 1000-1200 rpm for 15-30 min; then a crosslinking agent is added, and the mixture is stirred at 65-75°C and 1000-1200 rpm for 10-20 min; then dibutyltin dilaurate is added, and the mixture is stirred at 65-75°C and 1000-1200 rpm for 8-15 min; and the mixture is stirred at 55-65°C and 15-30 min under vacuum, and then the mixture is allowed to stand in a vacuum state for 20-30 min to obtain a silicone rubber material;

[0028] (3) The silicone adhesive is taken out and placed in a constant temperature box at 24-28° C. for aging for 20-25 hours. After aging, it is divided into packages and stored in a sealed container at room temperature and away from light to obtain a thermally conductive silicone adhesive.

[0029] Beneficial effects of the present invention:

[0030] 1. Compared with the prior art, the present invention adopts hydroxyl-terminated polydimethylsiloxane, fumed silica, vinyl silicone oil, hydrogen-containing silicone oil, composite thermal conductive material, crosslinking agent, γ-glycidyloxypropyltrimethoxysilane, dibutyltin dilaurate, etc. as raw materials to prepare thermal conductive silicone adhesive. By using the raw materials in a coordinated manner and making reasonable proportions, the prepared silicone adhesive has excellent thermal conductivity, mechanical properties and high temperature resistance, greatly improving the aging resistance and durability of the silicone adhesive, which is conducive to the wide application of thermal conductive silicone adhesive.

[0031] 2. The present invention prepares modified hexagonal boron nitride by composite modification of polysaccharides and polydopamine, simultaneously carbonizing plant fibers to obtain carbonized fibers, and introducing an extract from Morinda officinalis leaves into a CuSO4·5H2O aqueous solution for mixed reaction to prepare CuO NPs. The prepared modified hexagonal boron nitride, carbonized fibers, and CuO NPs are then synergistically incorporated into the preparation of a silicone adhesive as a composite thermally conductive material to produce a thermally conductive silicone adhesive. The introduction of the composite thermally conductive material not only improves the thermal conductivity of the silicone adhesive but also its mechanical properties and high-temperature resistance. Furthermore, the CuO NPs impart excellent antibacterial properties to the silicone adhesive, significantly enhancing its durability. DETAILED DESCRIPTION

[0032] Parameters for specific chemical substances used, sources.

[0033] Hydroxyl terminated polydimethylsiloxane, Model: MY 107V80000, Viscosity (25℃, mm 2 / s): 81000, from Anhui Mingyi Silicon Industry Co., Ltd.;

[0034] Fumed silica, model: TH-a200, brand: Wanhua Tianhe;

[0035] Vinyl silicone oil, model: HY-300, from Dongguan Huayue Technology Co., Ltd.

[0036] Hydrogenated silicone oil, model 202, from Dongguan Airui Chemical Co., Ltd.

[0037] Karstedt's catalyst, commercially available, CAS number: 68478-92-2;

[0038] Sucrose, commercially available;

[0039] Chitosan oligosaccharide, commercially available;

[0040] Flax fiber, commercially available;

[0041] Hexagonal boron nitride, particle size: 20 μm, commercially available;

[0042] Preparation of neem leaf extract: Fresh neem leaves (commercially available) were washed, dried, crushed, and passed through a 60-mesh sieve for later use; neem leaves were mixed with water at a solid-liquid ratio of 1:16 and then extracted, and ultrasonic extraction was performed at an ultrasonic frequency of 60 kHz, a power of 300 W, and a temperature of 60°C for 45 minutes; the extraction was repeated twice; after the extraction was completed, the extract was filtered through a 0.22 μm microporous filter membrane, the filtrate was collected and concentrated under reduced pressure (50°C, vacuum degree 0.08 MPa) to 1 / 5 of the original volume, and then placed at 60°C for vacuum drying for 24 hours to obtain the neem leaf extract.

[0043] Preparation of Morinda citrifolia leaf extract: Fresh Morinda citrifolia leaves (commercially available) were washed, dried, crushed, and passed through an 80-mesh sieve for later use; the Morinda citrifolia leaves were mixed with water at a solid-liquid ratio of 1:15 and then extracted. Ultrasonic extraction was performed at an ultrasonic frequency of 50 kHz, a power of 300 W, and a temperature of 50°C for 40 min; the extract was then filtered through a 0.22 μm microporous membrane, and the filtrate was concentrated under reduced pressure (40°C, a vacuum degree of 0.08 MPa) to 1 / 4 of the original volume, and then vacuum-dried at 65°C for 24 h to obtain the Morinda citrifolia leaf extract.

[0044] Example 1

[0045] A method for preparing a thermally conductive silicone adhesive comprises the following steps:

[0046] (1) Place 25 parts by weight of the composite thermal conductive material in a ball mill, add 4mm zirconium oxide ball milling beads to 1 / 4 of the ball mill volume, and disperse for 30 minutes under the assistance of 40kHz ultrasound to obtain a pretreated composite thermal conductive material; then mix the pretreated composite thermal conductive material and 5 parts by weight of γ-glycidyloxypropyltrimethoxysilane at 1000rpm and 50℃ for 10 minutes to obtain a mixture 1; add the mixture 1 to a reactor, add 100 parts by weight of hydroxyl-terminated polydimethylsiloxane and 25 parts by weight of fumed silica in sequence, mix and stir at 300rpm for 5 minutes, then increase the speed to 1200rpm and mix and stir for 20 minutes; then maintain the speed of 1200rpm, evacuate to 0.09MPa, heat to 80℃, and continue stirring for 25 minutes to obtain a mixture 2;

[0047] (2) 6 parts by weight of vinyl silicone oil and 4 parts by weight of hydrogenated silicone oil were mixed with mixture 2, vacuumed to 0.09 MPa, and stirred at 80°C and 1000 rpm for 20 minutes; then 0.001 parts by weight of Karstedt' catalyst were added, and the mixture was stirred at 80°C and 1000 rpm for 30 minutes; then 4 parts by weight of cross-linking agent were added, vacuumed to 0.09 MPa, and stirred at 70°C and 1000 rpm for 20 minutes; then 0.3 parts by weight of dibutyltin dilaurate were added, and the mixture was stirred at 70°C and 1000 rpm for 10 minutes; and vacuumed to 0.08 MPa, and stirred at 60°C for 20 minutes, and then the mixture was kept in a vacuum state and allowed to stand for 30 minutes to obtain a silicone rubber material;

[0048] (3) Take out the silicone adhesive, place it in a constant temperature box at 25°C for 24 hours, package it after aging, and store it in a sealed container at room temperature away from light to obtain a thermally conductive silicone adhesive.

[0049] The crosslinking agent is prepared by mixing methyltrimethoxysilane and vinyltriethoxysilane in a weight ratio of 2.5:1.

[0050] The composite thermal conductive material is prepared by mixing modified hexagonal boron nitride and CuO NPs nanomaterials in a weight ratio of 5:1.

[0051] The preparation method of the modified hexagonal boron nitride comprises the following steps:

[0052] Hexagonal boron nitride and sucrose were evenly mixed in a weight ratio of 1:5 and placed in a ball mill. 4mm zirconia ball milling beads were added to 1 / 4 of the volume of the ball mill, and then ball milled at a speed of 20 Hz for 10 hours. The ball milled product was then washed three times with water and centrifuged at 5000 rpm for 10 minutes. The precipitate was collected and vacuum dried at 45°C to obtain modified hexagonal boron nitride.

[0053] The preparation method of the CuO NPs nanomaterial comprises the following steps:

[0054] 2.5 parts by weight of CuSO4·5H2O were mixed with 100 parts by weight of water, followed by the addition of 50 parts by weight of Morinda citrifolia leaf extract. The pH was maintained at 7.0 with a 0.1 mol / L NaOH aqueous solution, and the solution was mixed and reacted at 70°C and 500 rpm for 5 hours to obtain a mixed solution. The mixed solution was centrifuged at 1000 rpm for 24 hours, and the solid precipitate was washed three times with water and then with anhydrous ethanol, and then dried in vacuo at 60°C for 4 hours to obtain CuO NPs nanomaterials.

[0055] Example 2

[0056] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is formed by mixing modified hexagonal boron nitride and CuO NPs nanomaterials in a weight ratio of 5:1;

[0057] The preparation method of the modified hexagonal boron nitride comprises the following steps:

[0058] Hexagonal boron nitride and chitosan oligosaccharide were mixed evenly in a ball mill at a weight ratio of 1:5, and placed in a ball mill. 4mm zirconium oxide ball milling beads were added to 1 / 4 of the volume of the ball mill, and then ball milled at a speed of 20 Hz for 10 hours. The ball milled product was then washed three times with water, and then centrifuged at 5000 rpm for 10 minutes. The precipitate was collected and vacuum dried at 45°C to obtain modified hexagonal boron nitride.

[0059] The preparation method of the CuO NPs nanomaterial is consistent with that in Example 1.

[0060] Example 3

[0061] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is formed by mixing modified hexagonal boron nitride and CuO NPs nanomaterials in a weight ratio of 5:1;

[0062] The preparation method of the modified hexagonal boron nitride comprises the following steps:

[0063] Hexagonal boron nitride and chitosan oligosaccharide were mixed evenly in a weight ratio of 1:5 and placed in a ball mill, 4mm zirconium oxide ball milling beads were added to 1 / 4 volume of the ball mill, and then ball milled at a speed of 20 Hz for 10 hours; the ball milled product was then washed three times with water, and then centrifuged at 5000 rpm for 10 minutes, the precipitate was collected, and vacuum dried at 45°C to obtain a mixture; the mixture was immersed in a dopamine solution and mixed and stirred for 5 hours, wherein the immersion material-liquid ratio was 1:12 (g:mL), and then vacuum dried to obtain polydopamine composite modified hexagonal boron nitride.

[0064] The dopamine solution is obtained by mixing 0.05 parts by weight of dopamine hydrochloride with 25 parts by weight of Tris buffer (pH=7.8).

[0065] The preparation method of the CuO NPs nanomaterial is consistent with that in Example 1.

[0066] Example 4

[0067] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is formed by mixing modified hexagonal boron nitride and carbonized fiber in a weight ratio of 5:2;

[0068] The preparation method of the modified hexagonal boron nitride is consistent with that of Example 3.

[0069] The preparation method of the carbonized fiber comprises the following steps:

[0070] The flax fibers were placed in a tubular furnace and carbonized under an argon atmosphere. The carbonization process was as follows: heating from room temperature to 120°C at a heating rate of 10°C / min and holding for 1 hour; then heating from 120°C to 360°C at a heating rate of 5°C / min and holding for 3 hours; and finally heating to 1000°C at a heating rate of 3°C / min and holding for 2 hours.

[0071] Example 5

[0072] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is prepared by mixing modified hexagonal boron nitride, carbonized fiber, and CuO NPs nanomaterials in a weight ratio of 5:2:1;

[0073] The preparation method of the modified hexagonal boron nitride is consistent with that of Example 3.

[0074] The preparation method of the carbonized fiber is consistent with that of Example 4.

[0075] The preparation method of the CuO NPs nanomaterial comprises the following steps:

[0076] 2.5 parts by weight of CuSO4·5H2O were mixed with 100 parts by weight of water, followed by the addition of 50 parts by weight of neem leaf extract. The pH was maintained at 7.0 with a 0.1 mol / L aqueous NaOH solution, and the solution was mixed and reacted at 70°C and 500 rpm for 5 hours to obtain a mixed solution. The mixed solution was centrifuged at 1000 rpm for 24 hours, and the solid precipitate was washed three times with water and then with anhydrous ethanol, and then dried in vacuo at 60°C for 4 hours to obtain CuO NPs nanomaterials.

[0077] Example 6

[0078] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is prepared by mixing modified hexagonal boron nitride, carbonized fiber, and CuO NPs nanomaterials in a weight ratio of 5:2:1;

[0079] The preparation method of the modified hexagonal boron nitride is consistent with that of Example 3.

[0080] The preparation method of the carbonized fiber is consistent with that of Example 4.

[0081] The preparation method of the CuO NPs nanomaterial is consistent with that in Example 1.

[0082] Comparative Example 1

[0083] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is formed by mixing modified hexagonal boron nitride, carbon fiber, and nano-copper oxide in a weight ratio of 5:2:1;

[0084] The preparation method of the modified hexagonal boron nitride is consistent with that of Example 3.

[0085] The preparation method of the carbonized fiber is consistent with that of Example 4.

[0086] The nano copper oxide is commercially available (spherical, model: ML-CuO-N30, particle size 30 nanometers, Zhejiang Manli Nanotechnology Co., Ltd.).

[0087] Comparative Example 2

[0088] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is formed by mixing modified hexagonal boron nitride and carbonized fiber in a weight ratio of 5:2;

[0089] The preparation method of the modified hexagonal boron nitride is consistent with that of Example 2.

[0090] The preparation method of the carbonized fiber is consistent with that of Example 4.

[0091] Comparative Example 3

[0092] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is modified hexagonal boron nitride;

[0093] The preparation method of the modified hexagonal boron nitride is consistent with that of Example 2.

[0094] Comparative Example 4

[0095] A method for preparing a thermally conductive silicone adhesive, which differs from Example 1 in that the composite thermally conductive material is hexagonal boron nitride.

[0096] Test Example 1

[0097] Thermal conductivity

[0098] The thermally conductive silicone adhesives prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to performance tests. The thermal conductivity was measured using a thermal conductivity tester (model DRE-2C, Xiangtan Instrument Co., Ltd.) with reference to ASTM D5470-17 (2024) "Standard test method for thermal transmission properties of thermally conductive electrical insulation materials." The specific test results are shown in Table 1 below.

[0099] Table 1

[0100]

[0101]

[0102] As shown in Table 1, by comparing Examples 1-6 with Comparative Example 1-4, it is found that the thermal conductivity of Examples 1-6 and Comparative Example 1-3 is higher than that of Comparative Example 4; by comparing Examples 1-6 with Comparative Example 1-3, it is found that the thermal conductivity of Examples 4-6 and Comparative Example 1-3 is higher than that of Example 1-3; by comparing Examples 4-6 with Comparative Example 1-3, it is found that Example 6 has the highest thermal conductivity and has better thermal conductivity. The reason for this may be that the hexagonal boron nitride modified with chitosan oligosaccharide and polydopamine has improved dispersion in the matrix and has a higher in-plane thermal conductivity. The introduction of carbonized fiber and its coordinated use form a rich heat conduction channel, which can better make up for the lack of thermal conductivity of the modified hexagonal boron nitride in the vertical direction and is beneficial to improving the thermal conductivity of the silicone adhesive. At the same time, CuO The introduction of NPs can fill the tiny gaps between fillers, helping to connect discrete modified hexagonal boron nitride sheets and carbon fibers, forming a continuous thermal conductivity path and reducing interfacial thermal resistance. This creates a stable heat conduction channel and improves the thermal conductivity of silicone adhesives. Compared to polysaccharide-modified hexagonal boron nitride, hexagonal boron nitride modified with a combination of chitosan oligosaccharide and polydopamine promotes orderly overlap with carbon fibers, preventing agglomeration and forming a more effective thermal network, thereby improving thermal conductivity.

[0103] Test Example 2

[0104] Performance Testing

[0105] In order to test the high temperature resistance of the thermally conductive silicone adhesives prepared in Examples 1-6 and Comparative Examples 1-4, metal bonding specimens were prepared using the thermally conductive silicone adhesives prepared in Examples 1-6 and Comparative Examples 1-4 as adhesives, with reference to the national standard "GB / T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material)". LY-12 aluminum alloy was selected as the bonding metal. Each bonding specimen was hung in a free state in a hot air aging box. The interval between specimens should be greater than 5 mm, and the interval between the specimen and the box wall of the hot air aging box should be greater than 70 mm. The heat aging temperatures were selected at 100°C, 150°C, and 200°C, respectively, and the heat treatment time was selected at 5 h. After the heat treatment, the specimens were placed at room temperature for 24 h, and then the shear strength and other properties were tested according to the national standard "GB / T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material)".

[0106] The test results are averaged. The specific test results are shown in Table 2.

[0107] Table 2 Test results of high temperature resistance of each sample

[0108]

[0109] As can be seen from Table 2, by comparing Examples 1-6 with Comparative Example 1-4, it is found that the tensile shear strength of Examples 1-6 and Comparative Example 1-3 is higher than that of Comparative Example 4; by comparing Examples 1-6 with Comparative Example 1-3, it is found that the tensile shear strength of Examples 4-6 and Comparative Example 1-3 is higher than that of Example 1-3; by comparing Examples 4-6 with Comparative Example 1-3, it is found that Example 6 has the highest tensile shear strength and has better mechanical properties. The reason for this may be that hexagonal boron nitride can react with hydroxyl-terminated polydimethylsiloxane after modification with chitosan oligosaccharide and polydopamine, significantly improving the compatibility and interfacial bonding with the matrix. At the same time, the flax fiber forms a graphitized structure after high-temperature carbonization, which can be used as a fiber reinforcement phase to withstand tension and form a "fiber-matrix" reinforcement network with the matrix, greatly improving the tensile properties, and can reduce the agglomeration of CuO NPs nanoparticles in the matrix, improve its dispersibility, and thus improve the tensile shear strength of the silicone adhesive.

[0110] As shown in Table 2, by comparing Examples 1-6 with Comparative Examples 1-4, it is found that after heat treatment, the decrease in tensile shear strength of Example 4 and Comparative Example 2 is significantly greater than that of the other Examples and Comparative Examples, and the decrease in tensile shear strength of Example 6 is the smallest, which shows good high temperature resistance, long service life at high temperatures, and good anti-aging performance. Analysis shows that the reason may be that the introduction of CuO NPs nanomaterials can reduce the thermal oxidative degradation of the silicone adhesive matrix at high temperatures and can also act as an "interface bridging agent" to increase the interfacial bonding force between the modified hexagonal boron nitride and carbonized fiber and the matrix at high temperatures, thereby stabilizing the filler-matrix interface and inhibiting interfacial thermal decomposition, thereby improving the high temperature resistance of the silicone adhesive. However, silicone adhesives without the addition of CuO NPs nanomaterials are more susceptible to matrix degradation and structural damage at high temperatures due to the lack of effective antioxidant protection and interface stabilization mechanisms, resulting in poor high temperature resistance.

Claims

1. A thermally conductive silicone adhesive, characterized in that: The invention comprises the following components in parts by weight: 100-120 parts of hydroxyl-terminated polydimethylsiloxane, 20-30 parts of fumed silica, 5-8 parts of vinyl silicone oil, 3-5 parts of hydrogenated silicone oil, 0.001-0.002 parts of platinum catalyst, 20-30 parts of composite thermal conductive material, 3-5 parts of crosslinking agent, 3-8 parts of γ-glycidyloxypropyltrimethoxysilane, and 0.1-0.5 parts of dibutyltin dilaurate; The composite thermal conductive material is selected from at least two of modified hexagonal boron nitride, carbonized fiber, and CuO NPs nanomaterials; The modified hexagonal boron nitride is hexagonal boron nitride modified with polysaccharide; or hexagonal boron nitride modified with polysaccharide and polydopamine; The carbonized fiber is prepared by placing plant fiber in a tube furnace and performing a carbonization treatment under an argon atmosphere; The CuO NPs nanomaterial is prepared by using neem leaf extract or Morinda officinalis leaf extract as a stabilizer.

2. The thermally conductive silicone adhesive according to claim 1, wherein: The preparation method of the modified hexagonal boron nitride comprises the following steps: Hexagonal boron nitride and polysaccharide are mixed uniformly in a weight ratio of 1:4-6 and placed in a ball mill jar. 3-5 mm zirconium oxide ball milling beads are added to 1 / 3-1 / 4 of the volume of the ball mill jar, and then ball milled at a speed of 15-20 Hz for 8-12 hours. The ball milled product is then washed with water 2-3 times, and then centrifuged at 4000-6000 rpm for 8-12 minutes. The precipitate is collected and vacuum dried at 40-50° C. to obtain modified hexagonal boron nitride. Alternatively, hexagonal boron nitride and polysaccharide are mixed evenly in a weight ratio of 1:4-6 and placed in a ball mill, 3-5 mm zirconium oxide ball milling beads are added to 1 / 3-1 / 4 of the volume of the ball mill, and then ball milled at a speed of 15-20 Hz for 8-12 hours; the ball milled product is then washed with water 2-3 times, and then placed at 4000-6000 rpm for 8-12 minutes. The precipitate is collected and vacuum dried at 40-50 ° C to obtain a mixture; the mixture is immersed in a dopamine solution and mixed and stirred for 3-6 hours, wherein the immersion material-liquid ratio is 1:10-13, and then vacuum dried to obtain modified hexagonal boron nitride.

3. The thermally conductive silicone adhesive according to claim 2, wherein: The polysaccharide is selected from sucrose and chitosan oligosaccharide.

4. The thermally conductive silicone adhesive according to claim 2, wherein: The dopamine solution is obtained by mixing dopamine hydrochloride and Tris buffer in a weight ratio of 0.05-0.15:

25.

5. The thermally conductive silicone adhesive according to claim 1, wherein: The preparation method of the CuO NPs nanomaterial comprises the following steps, calculated by weight: 2-4 parts of CuSO4·5H2O are mixed with 90-110 parts by weight of water, followed by adding 45-50 parts by weight of a plant extract, and maintaining the pH at 6.8-7.2 with a 0.1-0.2 mol / L NaOH aqueous solution. The solution is then mixed and reacted at 65-75°C and 400-600 rpm for 3-6 hours to obtain a mixed solution. The mixed solution is centrifuged at 800-1200 rpm for 20-25 hours, and the solid precipitate is washed 2-3 times with water and anhydrous ethanol in sequence, and then vacuum dried at 55-65°C for 3-5 hours to obtain CuO NPs nanomaterials.

6. The thermally conductive silicone adhesive according to claim 5, characterized in that: The plant extract is selected from one of neem leaf extract and Morinda officinalis leaf extract.

7. The thermally conductive silicone adhesive according to claim 1, wherein: The plant fiber is selected from flax fiber, ramie fiber and bamboo fiber.

8. The thermally conductive silicone adhesive according to claim 1, wherein: The crosslinking agent is prepared by mixing methyltrimethoxysilane and vinyltriethoxysilane in a weight ratio of 2-3:

1.

9. A method for preparing the thermally conductive silicone adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) placing the composite thermal conductive material in a ball mill and dispersing it under the assistance of 20-50kHz ultrasound for 20-30min to obtain a pretreated composite thermal conductive material; then mixing the pretreated composite thermal conductive material and γ-glycidyloxypropyltrimethoxysilane at 1000-1500rpm and 45-60°C for 8-12min to obtain a mixture 1; adding the mixture 1 to a reactor, adding hydroxyl-terminated polydimethylsiloxane and fumed silica in sequence, mixing and stirring at 200-500rpm for 3-8min, then increasing the speed to 1000-1500rpm and mixing and stirring for 15-30min; then maintaining the speed of 1000-1500rpm, continuing to stir under vacuum at 75-85°C for 15-30min to obtain a mixture 2; (2) Vinyl silicone oil and hydrogenated silicone oil are mixed with mixture 2, and the mixture is stirred under vacuum at 75-85°C and 1000-1200 rpm for 15-30 min; then a platinum catalyst is added, and the mixture is stirred at 75-85°C and 1000-1200 rpm for 15-30 min; then a crosslinking agent is added, and the mixture is stirred at 65-75°C and 1000-1200 rpm for 10-20 min; then dibutyltin dilaurate is added, and the mixture is stirred at 65-75°C and 1000-1200 rpm for 8-15 min; and the mixture is stirred at 55-65°C and 15-30 min under vacuum, and then the mixture is allowed to stand in a vacuum state for 20-30 min to obtain a silicone rubber material; (3) The silicone adhesive is taken out and placed in a constant temperature box at 24-28° C. for aging for 20-25 hours. After aging, it is divided into packages and stored in a sealed container at room temperature and away from light to obtain a thermally conductive silicone adhesive.